Microgrooved plasmonic bottle microresonator. (May 2015) - Nasir, M N Mohd; Ding, M; Murugan, G S; Zervas, M N
Abstract: In this paper, we demonstrate an enhancement to SPW cavity through the incorporation of high-Q WGM bottle microresonator (BMR) with surface microgrooves. A standard BMR fabricated through the "soften-and-compress" technique with initial length of 280 μm, bottle diameter of 187 μm and stem diameter of 125 μm was utilized in the experiment for supporting WGMs. Thin gold film was deposited on top of the BMR for generating SPWs. 21 microgrooves was then inscribed on the metal surface of the BMR along the azimuthal direction with 10 μm length, 485 nm width, 6 μm depth and pitch of 1.5 μm. Due to surface curvature, the gold film only covered half of the BMR with a characteristic meniscus shape and maximum thickness of 30 nm. The meniscus provides appropriately tapered metal edges that facilitate the adiabatic transformation of BMR WGMs to SPWs and vice-versa. Lorentzian shape-line fit performed on the TM excited resonances show that plasmonic Q values in excess of 4000 could be achieved from such structure with ∼ 25% coupling efficiency.